Risk factors for tooth loss in middle and older age after up to 10 years: an observational cohort study - Hassel, Alexander J.; Safaltin, Volkan; Grill, Sabine Katharina; Schröder, Johannes; Wahl, Hans-Werner; Klotz, Anna-Luisa; Habibi, Edriss; Rammelsberg, Peter; Zenthöfer, Andreas (Archives of oral biology, 2018)
Objective: The objective of this research was to identify risk factors for tooth loss in two birth cohorts, quinquagenarians and septuagenarians, after up to 10 years of clinical observation. Design: One hundred and twenty-three participants were recruited from the Interdisciplinary Study of Adult Development (ILSE) and examined at baseline and up to 10 years after. Thirty-nine and 84 participants belonged to the older (OC; born in 1930/32) cohort and younger (YC; born in 1950/52) cohort, respectively. Each participant underwent a dental examination comprising evaluation of the dental status (number of teeth, prosthetic restorations), Plaque Index (PI), Gingival Index (GI), DMF-S, periodontal probing depths (PD) and tooth mobility (TM). Incidence of tooth loss over the study period was calculated for both cohorts as well as for the grouped dental target variables. A logistic regression model for tooth loss (0=tooth present/1=tooth lost) was compiled with possible binary confounders. Results: During the study period (eight years in mean), 1.2 (1.9) and 2.6 (2.6) teeth were lost in YC and OC, respectively, reflecting correspondent loss rates of 5% and 14% (p<0.001). However, primarily TM >1 merged into substantial tooth loss (60% lost). The regression analysis confirmed the bivariate findings. Older age and worse oral health issues were identified as risk factors for tooth loss(p<0.05). Conclusions: Both quinquagenarians and septuagenarians show relevant tooth loss over a period of up to 10 years but more in septuagenarians. The predominant predictor for tooth loss seems to be greater tooth mobility. With the rising challenges due to aging in several societies, knowing the risks might help clinicians when weighing treatment strategies and should encourage refining preventive measures for older patients.